Academic Ethics in the Age of AI: A case study at STKIP DDI Pinrang - Walid, Abdul; Masri, Mawardi Jalil; Sulaiman, Sulaiman; Aris, Nurul Amalia; Nurhandayani, Nurhandayani (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2025)
This study explores the extent of Artificial Intelligence (AI) usage among students and its implications for academic ethics, with a specific focus on STKIP DDI Pinrang. Employing a mixed-methods approach, quantitative data were collected through Likert-scale questionnaires distributed to 40 students, while qualitative insights were gathered via interviews with selected respondents. The findings indicate that students’ AI usage is very high (mean score: 4.45), particularly through tools such as ChatGPT, Grammarly, and Quillbot. However, their ethical awareness remains moderate, both in terms of understanding academic ethics (3.1562) and awareness of the ethical implications of AI use (3.04). Correlation analysis reveals a negative relationship between the intensity of AI usage and students' ethical perceptions. Thematic analysis of interviews confirms that students tend to use AI as a substitute rather than a support, and lack institutional guidance on its ethical boundaries. These findings highlight a critical gap between technological proficiency and ethical literacy. The study recommends integrating digital ethics education across curricula and establishing clear institutional policies to ensure responsible AI use in academic settings.